Population structure of Carex dioica L. (Cyperaceae) in Ukraine under different growth conditions - Sosnovska, Svitlana; Danylyk, Ivan (Biodiversity: Research and Conservation, 2017)
Under optimal growth conditions, the C. dioica populations were characterised by the prevalance of females compared to male ones (2:1), and under stress – a radical change in their sex ratio was observed towards a complete dominance of one of the genders. It was found that 50% of the studied C. dioica populations appeared to be thriving. Regardless of the vitality type of the population, the female individuals of this species, compared to male ones, realised their growth potential much better and, therefore, made a greater contribution to population vitality.